Maria Walecka-Garbalinska: Jules Lefèvre-Deumier (1797-1857) et le mythe romantique du Génie. Studia Romanica Upsaliensia 40. Almqvist & Wiksell International, Stockholm, 1987. 174 p. - Lund, Hans Peter (Revue Romane, 1987)
-